Delineating the importance of serum opsonins and the bacterial capsule in affecting the uptake and killing of Burkholderia pseudomallei by murine neutrophils and macrophages. - Minal Mulye; Michael P Bechill; William Grose; Viviana P Ferreira; Eric R Lafontaine; R Mark Wooten (Public Library of Science (PLoS), 2014)
Infection of susceptible hosts by the encapsulated Gram-negative bacterium Burkholderia pseudomallei (Bp) causes melioidosis, with septic patients attaining mortality rates ≥ 40%. Due to its high infectivity through inhalation and limited effective therapies, Bp is considered a potential bioweapon. Thus, there is great interest in identifying immune effectors that effectively kill Bp. Our goal is to compare the relative abilities of murine macrophages and neutrophils to clear Bp, as well as determine the importance of serum opsonins and bacterial capsule. Our findings indicate that murine macrophages and neutrophils are inherently unable to clear either unopsonized Bp or the relatively-avirulent acapsular bacterium B. thailandensis (Bt). Opsonization of Bp and Bt with complement or pathogen-specific antibodies increases macrophage-uptake, but does not promote clearance, although antibody-binding enhances complement deposition. In contrast, complement opsonization of Bp and Bt causes enhanced uptake and killing by neutrophils, which is linked with rapid ROS induction against bacteria exhibiting a threshold level of complement deposition. Addition of bacteria-specific antibodies enhances complement deposition, but antibody-binding alone cannot elicit neutrophil clearance. Bp capsule provides some resistance to complement deposition, but is not anti-phagocytic or protective against reactive oxygen species (ROS)-killing. Macrophages were observed to efficiently clear Bp only after pre-activation with IFNγ, which is independent of serum- and/or antibody-opsonization. These studies indicate that antibody-enhanced complement activation is sufficient for neutrophil-clearance of Bp, whereas macrophages are ineffective at clearing serum-opsonized Bp unless pre-activated with IFNγ. This suggests that effective immune therapies would need to elicit both antibodies and Th1-adaptive responses for successful prevention/eradication of melioidosis.